From CyBorD to dara-CyBorD, ASCT utilization trends in AL amyloidosis: a 15-year analysis - Eli Muchtar; Angela Dispenzieri; Francis K. Buadi; Prashant Kapoor; David Dingli; Taxiarchis V. Kourelis; Wilson Gonsalves; Nelson Leung; Suzanne R. Hayman; Martha Q. Lacy; Mustaqeem Siddiqui; Joselle Cook; et al. (Blood Advances)
Abstract: This retrospective analysis examined 15 years of autologous stem cell transplantation (ASCT) for light chain (AL) amyloidosis at the Mayo Clinic (2010-2024). We aimed to assess ASCT utilization trends, factors influencing practice changes, and current indications amid newer therapies. Four hundred and forty-one ASCTs were divided into cohort 1 (2010-2019) and cohort 2 (2020-2024), revealing a significant ASCT reduction in cohort 2 (385 vs 56, average 71% annual decrease). Cohort 2 patients were older, more likely to have relapsed/refractory disease, and had higher baseline bone marrow plasma cell burden compared to cohort 1. Pre-ASCT induction was more frequent in cohort 2 (89.3% vs 56.4%), with daratumumab (Dara)–cyclophosphamide-bortezomib-dexamethasone (CyBorD) replacing CyBorD as the predominant induction regimen. Lymphoma-based regimens were also more common in cohort 2 (15.1% vs 5.3%, P = .02). Day-100 satisfactory hematological response improved in cohort 2 (91.1% vs 72.7%, P = .001), although hematological complete response rates did not significantly differ (50.9% vs 38.8%, P = .09). In summary, there is a decrease in the utilization of ASCT in AL amyloidosis. This procedure is primarily reserved for patients with suboptimal responses, relapsed/refractory disease, lymphoplasmacytic clones (predominantly immunoglobulin M amyloidosis), or high bone marrow plasma cell burden (myeloma phenotype). This study underscores a significant shift in ASCT practice, driven by novel therapies, emphasizing more personalized management in AL amyloidosis.